Moral sentiments and reciprocal obligations: the case for pension fund investment in community development - Clark, G (Routledge, 2000)
Squeezed between increasing entitlement expenditures and static or declining real revenues, state-funded urban development is increasingly perceived as an unaffordable luxury. At the same time, the power and significance of the banking sector is giving way to new kinds of financial institutions that have little or no interest in community development. Not surprisingly, it is often argued that pension funds ought to be more sensitive to community needs. However, some analysts argue that pension funds are properly only the agents of plan beneficiaries; any investment that took into account community needs would be, in effect, an unjustified tax on individuals' future welfare. Furthermore, analysts are very doubtful about the integrity of public pension plan investment decision-making. In this paper, I set out a morally informed justification of public pension plan investment in community development. In doing so, I develop a model of community development that stresses the reciprocal nature of the obligations embedded in the relationship between the community and pension plan beneficiaries. This approach also has significant implications for a wide variety of private sponsored plans. The paper begins with an assessment of pension fund decision-making and the practices of the investment management industry, drawing upon related research on pension fund capitalism. It goes on to issues of social obligation, referencing recent research on the nature of social contracts. To give the analysis empirical relevance I refer to the much disputed decision of the West Virginia legislature to require their public pension funds' Investment Management Board to invest in the state government's corrections authority.